Comparative Analysis of FCAW, and GMAW Welding With Heat Input Variations on A36 Steel Against Vickers Hardness Test and Macrostructure - Herman Pratikno; Wimala Lalitya Dhanista; Nugraha Adhi Pahlawan (International Journal of Offshore and Coastal Engineering, 2021)
In offshore building construction, a precise welding method is needed on A36 steel, where A36 steel is one of the main materials in the fabrication process of offshore buildings. In this study a comparison of the results of the welding GMAW and FCAW with variations of the heat input on the A36 steel to the Hardness test, and the macrostructure test and the selection of the most appropriate method based on the results of the mechanical test analysis. The heat input variations used are GMAW 1.50 kJ / mm and 2.03 kJ / mm while for FCAW 1.90 kJ / mm and 2.30 kJ / mm. The results of this study are the best hardness test results are the FCAW welding method with a heat input of 2.30 kJ / mm with an average ultimate strength of 149.06 HVN, in the macro test the results show that the greater the heat input, the wider the HAZ area, this is shown by welding FCAW heat input 2.30 kj / mm which has a HAZ width area of 20 mm.